Establishing a church library for the Metro Manila Christian Church Quezon City sector - Ricafort, Patricia Ellis G. (School of Library and Information Studies, University of the Philippines Diliman, 2014)
The Metro Manila Christian Church (MMCC) is a non-denominational Christian group based in the National Capital Region of the Philippines. The Quezon City Sector (QC Sector) with a membership of around 350 individuals, not including teens and children who are not officially part of the roster, is one of its largest groups by geographical subdivision. Its continuous growth in membership is a contribution to the developing market of religious, spiritual, and inspirational literature. Recognizing the needs of members for an organized collection of religious, spiritual, and inspirational literature, this study sought to determine the requirements for establishing a church library for the MMCC QC Sector.